New Asian regionalism in international economic law - HSIEH, Pasha L. (Institutional Knowledge at Singapore Management University, 2022)
This book provides the first systematic analysis of new Asian regionalism as a paradigm shift in international economic law. It argues that new Asian regionalism has emerged amid the Third Regionalism and contributed to the New Regional Economic Order, which reinvigorates the role of developing countries in shaping international trade norms. To substantiate the claims, the book introduces theoretical debates and evaluates major regional economic initiatives and institutions, including the ASEAN+6 framework, APEC, the CPTPP and the RCEP. It also sheds light on legal issues involving the US-China trade war and the COVID-19 pandemic, as well as trade policies of Asian powers, the European Union and the United States. Hence, the legal analysis and case studies offer a fresh perspective of Asian integration and bridge the gap between academia and practice.